2018
DOI: 10.3390/land7010018
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Businesses and Land Reform: Corporatization or Transformation?

Abstract: Abstract:Inclusive businesses (IBs), embodying partnerships between commercial agribusinesses and smallholder farmers/low-income communities, are considered to contribute towards rural development and agricultural sector transformation. Structured as complex organizational set-ups consisting of, and overcoming the limitations of, standard inclusive instruments (collective organization, mentorship, supply contract, lease/management contract and equity), they allow for the inclusion of smallholders and low-incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The most significant benefit seems to come from gaining market access for beneficiaries who (initially) are not able to operate independently. Conversely, the commercial partner is able to control the IB, prioritising the business aspect over the developmental facet of the partnership (Chamberlain & Anseeuw, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most significant benefit seems to come from gaining market access for beneficiaries who (initially) are not able to operate independently. Conversely, the commercial partner is able to control the IB, prioritising the business aspect over the developmental facet of the partnership (Chamberlain & Anseeuw, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…There is no additional asset base beyond land that allows smallholders to enter onto a path to accumulation, which questions the potential for IBs to drive development. Indeed, ownership needs to be combined with effective capacitation of the beneficiaries, and the commercial partner needs to take cognisance of the need for shortterm financial rewards for these beneficiaries (Chamberlain & Anseeuw, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even those promoting value chains have found that they are not effective in reaching the poorest, as they tend to involve farmers who already have more assets and education [127,129,130]. Independent studies have found that incorporation into global markets happens on very unequal terms and can have extremely adverse consequences for farmers and workers [80,[131][132][133] and risk undermining the local and territorial markets that most farmers already sell to and where most food is traded [39,106]. The core issue is the very unequal power relations involved, which lead to more dependency and inequality, typically transforming peasants into workers on their own land by subordinating them to "the dominant frameworks of global agribusiness and capital accumulation" [134], p.21.…”
Section: Less Visible Forms Of Control Over Land and The Value Producedmentioning
confidence: 99%
“…Guo and Zhang supposed that the lack of an LCR payout mechanism is not conducive to either realizing the land rights of farmers settled in cities or the advancement of urbanization, and the inequality of new land rights could cause social conflicts [13]. Chamberlain's research proved that the reform of the land property rights system and the stability of farmers' property rights in South Africa contributed to the success of inclusive businesses [14].…”
Section: Current Researchmentioning
confidence: 99%